A Codesigned Compact Dual-Band Filtering Antenna with PIN Loaded for WLAN Applications - Shanxiong Chen; Yu Zhao; Maoling Peng; Yunji Wang (International Journal of Antennas and Propagation)
A codesigned compact dual-band filtering antenna incorporating a PIN diode for 2.45/5.2 GHz wireless local area network (WLAN) applications is proposed in this paper. The integrated filtering antenna system consists of a simple monopole radiator, a microstrip dual-band band-pass filter, and a PIN diode. The performance of the filtering antenna is notably promoted by optimizing the impedance between the antenna and the band-pass filter, with good selectivity and out-of-band rejection. The design process follows the approach of the synthesis of band-pass filter. In addition, the PIN diode is incorporated in the filtering antenna for further size reduction, which also widens the coverage of the bandwidth by about 230% for 2.4 GHz WLAN. With the presence of small size and good filtering performances, the proposed filtering antenna is a good candidate for the wireless communication systems. Prototypes of the proposed filtering antenna incorporating a PIN diode are fabricated and measured. The measured results including return losses and radiation patterns are presented.